Diversity of invertebrates consumed by the Yanomami and Yekuana communities from the Alto Orinoco, Venezuela - Araujo, Yelinda; Beserra, Paulo (Interciência, 2007)
Invertebrates represent a rich and tempting food for the indigenous people and play an important role in the diet of these populations. The aim of this work was to make the taxonomic identification of the invertebrate species consumed by the indigenous communities Yanomami and Yekuana from the Alto Orinoco region, Amazonas State, Venezuela. Open interviews were carried out and behavioral observation made of 27 males and 9 females from 12 to 70 years old. Larvae and adult specimens of invertebrates indicated and validated as eatable were collected alive and later identified. The Yanomami consume 20 and the Yekuana 28 species of invertebrates. The Yanomami eat mainly caterpillars, larvas of scarabs and wasps, termites, ants and spiders, while the Yekuana consume earthworms, shrimps, oysters and a variety of aquatic insects. The proximity of the Yekuana communities to rivers and streams has possibly contributed to the specialization of their rich diet in aquatic insects, unlike the Yanomami communities that consume mainly terrestrial invertebrates of forest origin. The strategy of the natives in the consumption of these small animals indicates that they have a detailed knowledge of their environment and of the use and manipulation of the forest resources, to provided food to the human populations without affecting biodiversity.
Diversidad de invertebrados consumidos por las etnias Yanomami y Yekuana del Alto Orinoco, Venezuela
Keywords: Animalsia; Araneae; Decapoda (crustacea); Formicidae; Hexapoda; Invertebrata; Isoptera; Ostreidae; Scarabaeus